Mikhail Kondratyev: When There is Only a Name on a Card - Marianna E. Sachkova; Nikita V. Kochetkov (Peoples' Friendship University of Russia (RUDN University), 2020)
The article is dedicated to the memory of an outstanding scientist, founder and dean of the Faculty of Social Psychology at the Moscow State University of Psychology and Education (MSUPE). Mikhail Yurievich Kondratyev was a well-known researcher and practitioner in the field of social psychology, including the problems of closed social groups, status structuring of communities of different types, relations of interpersonal significance, phenomena of power and authority, to mention just a few. He was also the author of over 300 educational, scientific and methodological publications on social, penitentiary, developmental and educational psychology.